Platelet Consumption in Thrombocythemia Complicated by Erythromelalgia: Reversal by Aspirin - Genderen, Perry J J Van; Michiels, Jan J; Strik, Roel Van; Lindemans, Jan; Van Vliet, Huub H D M (Thrombosis and Haemostasis, 1995)
The involvement of platelets in the pathogenesis of erythromelalgia, a frequent and characteristic microvascular thrombotic manifestation in patients with primary thrombocythemia and polycythemia rubra vera, was investigated by measuring the survival and turnover of 51Cr labeled autologous platelets in 10 patients with thrombocythemia complicated by erythromelalgia, in 10 asymptomatic thrombocythemia patients and in 6 subjects with reactive thrombocytosis. The mean platelet survival time of the erythromelalgia patients was 4.2 ± 0.2 days, which is significantly decreased as compared with asymptomatic thrombocythemia patients (6.6 ± 0.3 days, p <0.001) and patients with reactive thrombocytosis (8.0 ± 0.4 days, p <0.001). The mean platelet survival time of asymptomatic thrombocythemia patients was significantly decreased (p <0.01) as compared with reactive thrombocytosis patients. Treatment of erythromelalgia with aspirin increased the mean platelet survival time from 4.0 ± 0.3 days to 6.9 ± 0.4 days (p <0.001) and was associated with an elevation of the platelet count of 216 ± 30 × 109 platelets per liter (p <0.001). Coumadin failed to improve platelet survival or symptoms caused by erythromelalgia. The increased platelet consumption in erythromelalgia is attributed to the formation of platelet thrombi in the arterial microvasculature. This conclusion is supported by the ability of aspirin to interrupt platelet consumption and clinical features of erythromelalgia.